(untitled) (Bangladesh Journal of Pharmacology, 2015)
The advantageous effects of Vitis vinifera juice on depressive model mice were examined utilizing a blend of behavioral evaluations and biogenic amine neurotransmitter estimations. During the behavioral evaluations, immobility time on the forced swimming test and tail suspension test were measured in unstressed and immobilization-induced stressed mice. V. vinifera juice (4 mL/kg and 8 mL/kg) and fluoxetine (20 mg/kg) produced a significant decrease in immobility time of both unstressed and stressed mice when compared with their respective saline-treated control groups in both paradigms. Neurotransmitters were measured using high-performance liquid chromatography with electrochemical detector. V. vinifera juice raised the levels of both serotonin (p<0.001) and noradrenalin (p<0.001) in brain tissue. These outcomes give significant mechanistic insights into the protective effect of V. vinifera juice against depressive disorders. Our results showed that V. vinifera juice could relieve depressive manifestations in the rodent model of depression.